ARUS KAS OPERASI, KAPASITAS OPERASI DAN LIKUIDITAS TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2014-2020 - Koswara, Ayu Barokah; Rahmawati, Alda; Alifah, Azmi (Jaakes: Jurnal Akuntansi, Auditing, & Keuangan Syariah, 2022)
Financial distress is a problem that greatly affects the sustainability of the company. Early detection will reduce the possibility of company bankruptcy. This study aims to measure the effect of operating cash flow, operating capacity and liquidity as independent variables on financial distress as the dependent variable. The research method used in this research is descriptive quantitative. The results of this study indicate that the operating cash flow variable partially has no effect on financial distress with a coefficient value of 0.839. The operating capacity variable partially has no effect on financial distress with a coefficient value of 0.277. The liquidity variable partially affects financial distress with a coefficient value of 0.002. Simultaneously the operating cash flow variable, operating capacity has no effect on financial distress conditions with a coefficient value of 0.018. The coefficient of determination (R2) of 0.275 indicates that operating cash flow, operating capacity and liquidity only affect financial distress by 27%. It can be explained that financial distress is influenced by various factors, namely both internal and external factors. Managerial and operational failures that lead to inefficiency and ineffectiveness can cause serious financial problems for the company.